Molecular taxonomy of Pseudapocryptes (Bleeker, 1874) mudskippers from Sundarban mangroves, India. (2nd January 2017) - Mahadevan, G.; Ravi, V.; Bharathi, R.
Abstract: Background : More than 40 species of mudskipper is recorded worldwide, but the molecular taxonomy of very few species is studied so far. Objective : The objective of this study is to determine the molecular taxonomy and phylogenetic relationship of the Pseudapocryptes elongatus and Pseudapocryptes lanceolatus collected from the mudflats of Sundarban, India. Methods : The mitochondrial COI gene was sequenced to analyze the molecular taxonomy. The species name associated with the present analyzed sequence as shown by BLAST searches of GenBank was used to define the phylogenetic relationship. Results : Mitochondrial COI gene sequences of collected mudskippers were submitted to GenBank to get accession numbers. The BLAST search of GenBank matched 100% with the species name associated with the present analyzed sequence. Conclusions : The present study reveals the phylogenetic similarity between the species.